How has Brexit changed EU-UK trade flows? - Janez Kren; Martina Lawless (The Economic and Social Research Institute (ESRI), 2022)
This paper estimates how Brexit has affected goods trade between the United Kingdom and European Union. Using product-level trade flows between the EU and all other countries in the world as a comparison group, we find a sharp decline in trade from the UK to the EU and significant but smaller reductions in trade from the EU to the UK. However, when we estimate the size of the Brexit impact on trade using UK data and UK global trade as a benchmark, we find strikingly different results. We identify two key sources of this discrepancy. First, the UK's global exports grew relatively slowly. We argue these are not suitable as a no-Brexit counterfactual. Second, Brexit also led to breaks in the measurement of trade flows, particularly for the EU data. To resolve these issues, we combine UK-reported data for its trade with EU and EU data for its trade with the rest of the world to use as the appropriate benchmark for comparison. This generates an estimate that Brexit reduced trade by close to 20% in both directions.
Keywords: F10; 330; Brexit; free trade agreements; customs checks